Trách nhiệm xã hội và khả năng sinh lợi của các ngân hàng thương mại: Bằng chứng thực nghiệm tại Việt Nam - Nguyễn Quốc , Anh; Tăng Mỹ , Sang (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2021)
Currently, a good corporate social responsibility (CSR) implementation not only aids the bank’s long-term growth but also adds to society’s long-term growth. Through the collection of secondary data from 17 banks listed on two exchanges HOSE and HNX in the period from 2015 to 2020, the article has studied the impact of CSR on the profitability of listed banks in Vietnam. The research results show that most banks are paying more and more attention to these activities, in which activities related to human resources are being paid attention by all banks, activities in the remaining aspects have not been paid much attention. Quantitative research results have shown that bank profitability is related to financial leverage, bank size, and social responsibility activities related to human resources. Tobin’s Q coefficient is related to operating size and financial leverage. From the research results, three groups of related solutions have been proposed to increase the bank’s profitability.